GmYUC2a mediates auxin biosynthesis during root development and nodulation in soybean. (8th April 2019) - Wang, Youning; Yang, Wei; Zuo, Yanyan; Zhu, Lin; Hastwell, April H; Chen, Liang; Tian, Yinping; Su, Chao; Ferguson, Brett J; Li, Xia
Abstract : The auxin biosynthesis gene, GmYUC2a, is required for root and nodule development in soybean, showing that local auxin biosynthesis contributes significantly to determine nodule development. Abstract: Auxin plays central roles in rhizobial infection and nodule development in legumes. However, the sources of auxin during nodulation are unknown. In this study, we analyzed the YUCCA ( YUC ) gene family of soybean and identified GmYUC2a as an important regulator of auxin biosynthesis that modulates nodulation. Following rhizobial infection, GmYUC2a exhibited increased expression in various nodule tissues. Overexpression of GmYUC2a ( 35S::GmYUC2a ) increased auxin production in soybean, resulting in severe growth defects in root hairs and root development. Upon rhizobial infection, 35S::GmYUC2a hairy roots displayed altered patterns of root hair deformation and nodule formation. Root hair deformation occurred mainly on primary roots, and nodules formed exclusively on primary roots of 35S::GmYUC2a plants. Moreover, transgenic 35S::GmYUC2a composite plants showed delayed nodule development and a reduced number of nodules. Our results suggest that GmYUC2a plays an important role in regulating both root growth and nodulation by modulating auxin balance in soybean.